Mexican gothic - Moreno-Garcia, Silvia (New York : Del Rey, 2020)
After receiving a frantic letter from her newlywed cousin asking for help Noemí Taboada heads to High Place, a distant house in the Mexican countryside. Once there Noemi starts to dream of blood and doom. Trying to save her cousin Noemi uncovers stories of violence madness, and now mesmerized by High Place Noemi may find it impossible to ever escape the house.
Keywords: Debutantes -- Fiction; Cousins -- Fiction; Family secrets -- Fiction; Dreams -- Fiction; Dwellings -- Deterioration -- Fiction; Gothic fiction; Historical fiction